2021
DOI: 10.3390/ijerph182111233
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Residential Segregation, Later-Life Cognition, and Incident Dementia across Race/Ethnicity

Abstract: Systemic racism leads to racial/ethnic residential segregation, which can result in health inequities. We examined if the associations between residential segregation and later-life cognition and dementia differed based on segregation measure and by participant race/ethnicity. Tests of memory (n = 4616), language (n = 4333), visuospatial abilities (n = 4557), and incident dementia (n = 4556) were analyzed in older residents of Northern Manhattan, New York (mean age: 75.7 years). Segregation was measured at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 60 publications
3
27
0
Order By: Relevance
“…These findings partially mirror those of Pohl et al., who examined cross‐sectional associations between three segregation indices and memory, language, and visuospatial. 43 They found that Black participants living in segregated neighborhoods scored worse on language and memory. Irrespective of the participant's race/ethnicity, living in neighborhoods that were desegregated was associated with higher scores on the three cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…These findings partially mirror those of Pohl et al., who examined cross‐sectional associations between three segregation indices and memory, language, and visuospatial. 43 They found that Black participants living in segregated neighborhoods scored worse on language and memory. Irrespective of the participant's race/ethnicity, living in neighborhoods that were desegregated was associated with higher scores on the three cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that reported mixed findings have also considered the influence of neighborhood racial-ethnic composition and separation. Several studies indicate racial-ethnic composition and segregation may be differentially associated with cognitive outcomes depending on individual race/ethnicity, and such disparities in cognitive outcomes may be attributed to the downstream effects of structural racism (e.g., unequal distributions of wealth/resources) (Meyer et al, 2021; Pohl et al, 2021). In contrast, another study suggests Black neighborhood composition and Black-White segregation does not significantly influence cognitive aging (Kovalchik et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Another set of studies aimed to explore the associations between neighborhood racial-ethnic composition and cognitive decline; however, mixed findings were reported. One study found that neighborhood Black composition and Black-White segregation did not have a significant influence on cognitive aging (Kovalchik et al, 2015); whereas other studies found that individuals living in neighborhoods with a higher clustering of Black residents had slower declines over time on episodic memory (Meyer et al, 2021) and non-Hispanic Black adults were the most likely to experience negative effects of neighborhood segregation on cognition and dementia (Pohl et al, 2021). Among Hispanic older adults, one study found that higher neighborhood Hispanic composition and greater Hispanic-White segregation were significantly associated with faster cognitive decline (Kovalchik et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…African American/Black and Hispanic adults are more likely to develop Alzheimer’s disease (AD) than other racial groups, , which is a result of complex and interconnected factors related to structural and systemic racism, “lived experiences,” social determinants of health, comorbidities, and genetics. Reducing these disparities partially requires a better understanding of molecular changes in AD. Neuropathological differences in AD hallmarks (amyloid-β (Aβ) plaques and tau tangles) have not been reported in African American/Black and non-Hispanic White participants. , Some studies have observed that African American/Black participants are more likely to present with both AD and other dementia pathologies; , however, this may be dependent on the sampling of participants in the study in terms of community dwelling versus research centers. Moreover, potential molecular differences between African American/Black and non-Hispanic White participants have recently been reported, particularly in cerebrospinal fluid (CSF) levels of tau biomarkers for AD. , CSF levels of total tau and tau phosphorylated at position 181 (p-tau 181 ) were lower overall in African American/Black participants than non-Hispanic White participants regardless of cognitive status, , and furthermore, smaller changes in tau levels occurred in African American/Black participants with cognitive decline .…”
Section: Introductionmentioning
confidence: 99%